Glycoprotein B Antibodies Completely Neutralize EBV Infection of B Cells - Hong, Junping; Wei, Dongmei; Zhong, Ling; Wu, Qian; Chen, Kaiyun; Zhang, Wanlin; Yang, Yanbo; Chen, Junyu; Xia, Ningshao; Zhang, Xiao; Chen, Yixin (Frontiers in Immunology, 2022)
The Epstein–Barr virus (EBV) is the first reported oncogenic herpesvirus that establishes persistent infection in B lymphocytes in 95% of adults worldwide. Glycoprotein B (gB) plays a predominant role in the fusion of the viral envelope with the host cell membrane. Hence, it is of great significance to isolate gB-specific fusion-inhibiting neutralizing antibodies (NAbs). AMMO5 is the only gB NAb but fails to antagonize B-cell infection. It is essential to isolate potent NAbs that can completely block EBV infection of B cells. Using hybridoma technology and neutralization assay, we isolate two gB NAbs 8A9 and 8C12 that are capable of completely neutralizing B-cell infection in vitro. In addition, 8A9 shows cross-reactivity with rhesus lymphocryptovirus (rhLCV) gB. Competitive binding experiments demonstrate that 8A9 and 8C12 recognize novel epitopes that are different from the AMMO5 epitope. The epitopes of 8A9 and 8C12 are mapped to gB D-II, and the AMMO5 epitope is located precisely at gB aa 410–419. We find that 8A9 and 8C12 significantly inhibit gB-derived membrane fusion using a virus-free fusion assay. In summary, this study identifies two gB-specific NAbs that potently block EBV infection of B cells. Our work highlights the importance of gB D-II as a predominant neutralizing epitope, and aids in the rational design of therapeutics or vaccines based on gB.